2015
DOI: 10.1111/oik.02480
|View full text |Cite
|
Sign up to set email alerts
|

Leaf litter species identity alters the structure of pond communities

Abstract: The input of leaf litter resources is a major driver of ecosystem processes in terrestrial and freshwater habitats. Although variation exists in the quantity and composition of litter inputs due to natural and anthropogenic causes, few studies have examined how such variation influences the structure and composition of aquatic food webs. Using outdoor mesocosms, we examined the bottom–up effects of 10 chemically distinct tree litter species on microbial, algal, invertebrate and vertebrate fauna found in temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 52 publications
(74 reference statements)
4
47
0
Order By: Relevance
“…Several studies note that the performance of tadpoles and other consumers is positively correlated with litter nutrient content (Moran andHodson 1989, Cohen et al 2012). Thus, our study finds partial support for the notion that litter nutrient concentration is an important determinant of consumer biomass (Moran and Hodson 1989), yet we find support for the overriding effect of leached litter components in forest wetlands (Stephens et al 2013, Stoler andRelyea 2016). However, the effects of litter nutrients in their study were relatively weak compared to factors such as dissolved oxygen and phenolics, which parallels the findings of Stoler and Relyea (2016).…”
Section: Effects Of Diversity On Microbes Producers and Consumerssupporting
confidence: 60%
See 2 more Smart Citations
“…Several studies note that the performance of tadpoles and other consumers is positively correlated with litter nutrient content (Moran andHodson 1989, Cohen et al 2012). Thus, our study finds partial support for the notion that litter nutrient concentration is an important determinant of consumer biomass (Moran and Hodson 1989), yet we find support for the overriding effect of leached litter components in forest wetlands (Stephens et al 2013, Stoler andRelyea 2016). However, the effects of litter nutrients in their study were relatively weak compared to factors such as dissolved oxygen and phenolics, which parallels the findings of Stoler and Relyea (2016).…”
Section: Effects Of Diversity On Microbes Producers and Consumerssupporting
confidence: 60%
“…Biomass of wood frogs, survival of spring peepers, and mass at metamorphosis of spring peepers all increased with nutrient content. However, the effects of litter nutrients in their study were relatively weak compared to factors such as dissolved oxygen and phenolics, which parallels the findings of Stoler and Relyea (2016). For example, Kupferberg (1997) demonstrated that tadpole growth rate increases with algal protein content.…”
Section: Effects Of Diversity On Microbes Producers and Consumersmentioning
confidence: 67%
See 1 more Smart Citation
“…Because specialist relative species richness was highest under low canopy closure and low leaf litter accumulation, we conclude that many longleaf pine specialist amphibians require autotrophic wetlands driven by primary productivity (i.e., periphyton and phytoplankton) as opposed to heterotrophic wetlands driven by detrital input. Although detritus can be an important food source for amphibians (Altig et al , Stoler and Relyea ), or prey of amphibians (Earl and Semlitsch ), in the system we studied the negative effects of leaf litter on periphyton or phytoplankton growth (Kominoski et al , Stoler and Relyea ) likely outweigh potential benefits of leaf litter as a resource for most longleaf pine specialists. This is what one would expect if specialist species evolved in a pyric system.…”
Section: Discussionmentioning
confidence: 99%
“…On 13 July, we added 5 g of rabbit chow (Blue Bunny 16; Kent Nutrition Group) to each mesocosm to provide an initial source of organic nutrients that would normally be present in a natural wetland [24]. We placed a 60% shade cloth cover on each pool to simulate moderate canopy cover and to prevent oviposition of insects and frogs.…”
Section: Experimental Design and Setupmentioning
confidence: 99%